Biologic Mesh Reconstruction of the Pelvic Floor after Extralevator Abdominoperineal Excision: A Systematic Review - Alam, Nasra N.; Narang, Sunil K.; Köckerling, Ferdinand; Daniels, Ian R.; Smart, Neil J. (Frontiers in Surgery, 2016)
Introduction The aim of this review is to provide an overview of the evidence for the use of biologic mesh in the reconstruction of the pelvic floor after extralevator abdominoperineal excision of the rectum (ELAPE). Methods A systematic search of PubMed was conducted using the search terms ‘ELAPE’, ‘extralevator abdominoperineal excision of rectum’ or ‘extralevator abdominoperineal resection’. The search yielded 17 studies. Results Biologic mesh was used in perineal reconstruction in 463 cases. There were 41 perineal hernias reported but rates were not consistently reported in all studies. The most common complications were perineal wound infection (n = 93), perineal sinus and fistulae (n = 26) and perineal haematoma or seroma (n = 11). There were very few comparative studies, with only one RCT identified that compared patients undergoing ELAPE with perineal reconstruction using a biological mesh, with patients undergoing a conventional abdominoperineal excision of the rectum with no mesh. There was no significant difference in perineal hernia rates or perineal wound infections between the groups. Other comparative studies comparing the use of biologic mesh with techniques such as the use of myocutaneous flaps were of low quality. Conclusions Biologic mesh-assisted perineal reconstruction is a promising technique to improve wound healing and has comparable complications rates to other techniques. However, there is not enough evidence to support its use in all patients who have undergone ELAPE. Results from high-quality prospective RCTs and national/international collaborative audits are required.